Visualisasi Peta Budaya Cirebon dalam Mendukung Gerakan Ekonomi Kreatif Kota Cirebon - Risladiba, Risladiba; Ramdhani, Suciyadi (Jurnal Abdi Mas Adzkia, 2024)
This community service (PkM) aims to identify the material culture of Cirebon and produce a material culture map that can be accessed through the website so that it can be a reference data in the development of the creative economy in Cirebon. Through the Asset Based Community Development (ABCD) method, community service members carry out community service steps through appreciative inquiry, community maps, transects, and asset mapping to collect material culture information and produce output in the form of an interactive map of Cirebon's material culture. The results show that Cirebon is one of the regions that has rich local culture which has the potential to be developed into digital media that can be reached by the wider community. This potential development is realized in a website that contains an interactive map of Cirebon culture with the name Telusur Cirebon. Telusur Cirebon is a service community product that contains interactive map content, information cards (material culture), and a list of references that examine material culture. The creation of Telusur Cirebon provides an opportunity for sustainability of the PkM program because practically it has a role in: 1) presenting cultural data with easy-to-reach internet access; 2) ways to preserve or archive Cirebon's cultural riches; and 3) make it easier for academics (researchers/lecturers) to analyze research references in the form of journals/books about Cirebon culture which are available online (e-journals/e-books). Sustainability of the community service program can also be carried out through a collaboration scheme between LP2M IAIN Syekh Nurjati Cirebon, the government, local culture-based communities/institutions, and the private sector by continuing to complete data about Cirebon culture.